Design and Optimization of Lamellar Phase Change Composites for Thermal Energy Storage. Issue 1 (18th November 2020) - Tamraparni, Achutha; Hoe, Alison; Deckard, Michael; Zhang, Chen; Elwany, Alaa; Shamberger, Patrick J.; Felts, Jonathan R.
Abstract : Phase change materials offer thermal energy storage (TES) and are often integrated with high conductivity materials to increase power density. However, the design and optimization of such composites are historically based on intuition, as the computational techniques used to predict behavior in these systems are generally too expensive to perform parametric studies. Herein, a general design framework is developed and demonstrated that is optimized for TES in parallel lamellar structures, to identify the critical pitch required to treat the composite as a single effective medium and the optimum volume fraction of high conductivity material in the lamellar composite. The optimization criteria is tested experimentally using 3D printed AlSi12 alloy and octadecane. The composite system exhibits a critical pitch between a lamella of 1 mm and the optimum volume fraction for the high conductivity material is 0.6–0.8. The design principles demonstrated here show that the size and volumes of conductive materials are much larger than the current state of the art, and this framework provides a holistic approach to design for such future materials for TES applications. Abstract : High thermal conductivity materials are mixed with phase change materials to make composites with high thermal conductivity and high thermal energy storage capacity. Herein, a general design framework is developed for alternating lamellar structures that provide a simple way to determine the minimum pitch between lamella and the optimum volume fractions of each component based on the applied thermal load.